Detrimental effects of long sedentary bouts on the biomechanical response of cartilage to sliding. (3rd July 2020) - Graham, Brian T.; Moore, Axel C.; Burris, David L.; Price, Christopher
ABSTRACT: Purpose/Aim : Epidemiological evidence suggests, contrary to popular mythos, that increased exercise/joint activity does not place articular cartilage at increased risk of disease, but instead promotes joint health. One explanation for this might be activity-induced cartilage rehydration; where joint articulation drives restoration of tissue hydration, thickness, and dependent tribomechanical outcomes (e.g., load support, stiffness, and lubricity) lost to joint loading. However, there have been no studies investigating how patterning of intermittent articulation influences the hydration and biomechanical functions of cartilage. Materials and Methods : Here we leveraged the convergent stationary contact area (cSCA) testing configuration and its unique ability to drive tribological rehydration, to elucidate how intermittency of activity affects the biomechanical functions of bovine stifle cartilage under well-controlled sliding conditions that have been designed to model a typical "day" of human joint activity. Results : For a fixed volume of "daily" activity (30 min) and sedentary time (60 min), breaking up intermittent activity into longer and less-frequent bouts (corresponding to longer continuous sedentary periods) resulted in the exposure of articular cartilage to markedly greater strains, losses of interstitial pressure, and friction coefficients. Conclusions : These results demonstrated that the regularity of ex vivo activity regimens, specifically the duration of sedentary bouts, had a dominant effect on the biomechanical functions of articular cartilage. In more practical terms, the results suggest that brief but regular movement patterns ( e.g., every hour) may be biomechanically preferred to long and infrequent movement patterns ( e.g., a long walk after a sedentary day) when controlling for daily activity volume ( e.g ., 30 min).